Synthesis and Antimicrobial Activity of 3-(3-Phenylsulphonamidophenyl)-5-aryl-2-pyrazolines - Jamode, V.S.; Chandak, H.S.; Bhagat, P.R. (Asian Journal of Chemistry, 2010)
New 1-isonicontinoyl/carboxamido-3-(3-phenylsulphonamidophenyl)-5-aryl pyrazoline (2a–e/3a–e) have been synthesized by the action of isonicontinic acid hydrazide/semicarbazide hydrochloride with 1-(3-phenylsulphonamidophenyl)-3-aryl prop-2-ene-1-ones (1a–e) in pyridine medium. The synthesized compounds have been characterized by elemental analysis, IR and NMR spectral analysis and screened for antimicrobial activity.